2018
DOI: 10.11604/pamj.2018.29.140.13699
|View full text |Cite
|
Sign up to set email alerts
|

Corrélation radio-histologique des lésions mammaires ACR4: à propos de 181 cas et revue de la littérature

Abstract: RésuméLa classification Bi-Rads (Breast Imaging Reporting and Data System) de l'ACR (American College of Radiology) est le système de classement des images radiologiques, recommandé pour le dépistage du cancer du sein. La lésion ACR IV correspond à une anomalie indéterminée ou suspecte avec probabilité de malignité de 2-95% selon des études. Cette disparité nous a poussés à réaliser notre étudequi est uneétude rétrospective de 181 patientes étalée sur 5 ans, conduite dans le service de gynécologie-obstétrique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…The radio-histological correlation in our series shows that more than half of the breast lesions classified as BI-RADS 4 (52.54%) by imaging were cancers on histology. This result is approximately identical to the 52.7% cancer rate found by Zonderland et al in their prospective series where they assessed the diagnostic performance of mammography and ultrasound for breast cancer diagnosis using the BI-RADS final assessment categories by 12-month follow-up and histocytopathology correlation in the Netherlands 12 Our results are superior to those of Guennoun et al 10 in Morocco who had found a proportion of 29% of cancer in lesions classified BI-RADS 4. This difference is precisely the origin of the clarifications made in the fourth editions of the BI-RADS classification of the ACR which specifies subtypes 4a, 4b, and 4c.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The radio-histological correlation in our series shows that more than half of the breast lesions classified as BI-RADS 4 (52.54%) by imaging were cancers on histology. This result is approximately identical to the 52.7% cancer rate found by Zonderland et al in their prospective series where they assessed the diagnostic performance of mammography and ultrasound for breast cancer diagnosis using the BI-RADS final assessment categories by 12-month follow-up and histocytopathology correlation in the Netherlands 12 Our results are superior to those of Guennoun et al 10 in Morocco who had found a proportion of 29% of cancer in lesions classified BI-RADS 4. This difference is precisely the origin of the clarifications made in the fourth editions of the BI-RADS classification of the ACR which specifies subtypes 4a, 4b, and 4c.…”
Section: Discussionsupporting
confidence: 87%
“… 2 In addition, despite the immense progress in the treatment, the difficulty in the availability of anticancer molecules and their high costs compromise and darken the prognosis, leading to a high mortality linked to breast cancer in women. 9 , 10 The main risk factors linked to breast cancer are hormonal factors linked to premenopausal estrogen impregnation and genetic, behavioral, and environmental factors. 11 , 12 In Togo, a study carried out in 2016 on the epidemiology of cancers showed that breast cancer occupied the first rank.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study were by the study conducted on a total of 2817 patients which stated PPV FOR BIRADS 5 at 99.6% by Fu C et al[9] but they did not show the values of sensitivity and specificity. In contrast to this, there were papers by E. Lazarus et al[10] in which 381 patients were enrolled and A. Guennoun et al [11] in which 181 patients were enrolled which showed poor quality for BIRADS 3 and 4. We also found a paper that stated a higher diagnostic accuracy of BIRADS 4 than what we found authored by Hye-Jeong Lee et al [12] with a total of patients 136 in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Breast Imaging Recording and Data System (BIRADS) was developed by the American College of Radiology (ACR) to provide a uniform method for reporting mammography and breast imaging findings [5]. The BIRADS system uses a scale of categories ranging from 0 to 6 [11], each indicating a specific level of suspicion or recommendation for further evaluation. Highly suggestive of malignancy (biopsy strongly recommended) 6…”
Section: Introductionmentioning
confidence: 99%
“…L'atteinte du sein droit a été observée par Fofana [6] au Mali et par et Radesa [13] à Madagascar. Plusieurs auteurs [14,17,18] ont cependant trouvé dans leur étude une atteinte fréquente du sein gauche. L'atteinte mammaire bilatérale était observée chez 5,7% de nos patientes.…”
Section: Age (Année)unclassified